Fazlur Rahman's Concept Of Islamic Education And Its Relevance In The Modern Era - Yarun, Ayuningtias; Bakar, M. Yunus Abu; Fuad, Ah. Zakki (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The concept of education that is relevant today uses an applicative contextual approach. Fazlur Rahman in understanding the Qur'an sees it in a historical context and tries to project it in a contemporary context. The purpose of this study is to find out the concept of fazlur Rahman education and its relevance in modern times. The research method used by library research uses historical and philosophical analysis of the concept of Fazlur Rahman Islamic Education. Fazlur Rahman, a Hanafi-born Muslim intellectual, was born in the traditional community. However, his thinking is not stuck in the tradition that he studied a lot of Western sciences. Â Rahman is an Islamic modernist and reformer of Muslim education who contributes by offering more emphasized development strategies in areas that are part of the education system itself, as well as integrating the two sciences, so that there is no disintegration in education and there is no gap between sciences due to the dichotomy of education. Â Monitoring Fazlur Rahman's concept of education can be concluded his school of thought is stuck on the religious rational.